2018
DOI: 10.1111/joop.12218
|View full text |Cite
|
Sign up to set email alerts
|

Crafting a job in ‘tough times’: When being proactive is positively related to work attachment

Abstract: Employee work attachment has been found to predict many important work attitudes and behaviours. In this article, we hypothesize that job crafting will be positively associated with work attachment as indicated by psychological ownership of the job and affective organizational commitment. Moreover, drawing on theories and research on work meaning and work identity, we propose that the positive association between job crafting and work attachment will be stronger when employees experience tough times at work (i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
51
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(60 citation statements)
references
References 72 publications
6
51
0
3
Order By: Relevance
“…This is because, while previous studies looked at which circumstances could enhance the effectiveness of job crafting primarily [25,38], we demonstrated that even in the context of deficiencies, the effect of daily job crafting can be strengthened. Moreover, this is in line with Wang, Demerouti, Blanc, and Lu [39] found in a recent study that suggests that the advantages of job crafting will be more fortified during tough times, but this study further implies that job crafting can be an effective self-regulating behavior to manage daily motives and attitudes by capturing these phenomena at the within-person level as well. Therefore, it can be interpreted that our result is due to the nature of the job crafting, based on which we add the importance and value of job crafting to existing job crafting research flows.…”
Section: Theoretical Implicationssupporting
confidence: 91%
“…This is because, while previous studies looked at which circumstances could enhance the effectiveness of job crafting primarily [25,38], we demonstrated that even in the context of deficiencies, the effect of daily job crafting can be strengthened. Moreover, this is in line with Wang, Demerouti, Blanc, and Lu [39] found in a recent study that suggests that the advantages of job crafting will be more fortified during tough times, but this study further implies that job crafting can be an effective self-regulating behavior to manage daily motives and attitudes by capturing these phenomena at the within-person level as well. Therefore, it can be interpreted that our result is due to the nature of the job crafting, based on which we add the importance and value of job crafting to existing job crafting research flows.…”
Section: Theoretical Implicationssupporting
confidence: 91%
“…Rofcanin et al () indicated that the positive relationship of approach resources crafting (i.e., expansion‐oriented relational crafting) and work engagement was stronger for employees with lower impression management motives. In addition, research indicated that approach crafting might be more beneficial to employees who experience rough times, such that the positive relationship between approach crafting and work attachment was stronger for employees who were rated as poor performers or felt job insecurity (Wang, Demerouti, et al, ). Consistent with proactivity research, studies also found that contextual factors such as perceived organizational support (Cheng et al, ; Cheng & Yi, ) and autonomy support (Slemp et al, ) reinforced the relationship between approach crafting and employee well‐being.…”
Section: A Synthesized Nomological Network Of Antecedents and Consequmentioning
confidence: 99%
“…Although it is assumed that job crafting aims to benefit individuals themselves, approach crafting has also been found to benefit organizations because it is negatively related to turnover intentions (Esteves & Lopes, 2017b;Rudolph et al, 2017) and positively related to higher level of intention to stay (Rofcanin, Berber, Koch, & Sevinc, 2016), organizational commitment (Cheng et al, 2016;Rofcanin et al, 2016;Wang, Demerouti, Le Blanc, & Lu, 2018), and enhanced motivation to continue working beyond retirement age among older workers (Lichtenthaler & Fischbach, 2016b). With enhanced personjob fit and motivation as a result of approach crafting, it is not surprising that approach crafting is also associated with higher levels of task and contextual performance (Lichtenthaler & Fischbach, 2016a;Rofcanin, Bakker, Berber, Gölgeci, & Las Heras, 2018;Rudolph et al, 2017).…”
Section: Outcomes Of Approach Craftingmentioning
confidence: 99%
“…Previous studies have revealed the effectiveness of empowering leadership in a Chinese context [ 32 ]. Additionally, individual job crafting occurs also in collectivistic cultures like China [ 46 ]. Nevertheless, we suggest that future research in other cultural contexts is needed to verify the generalizability of our findings.…”
Section: Discussionmentioning
confidence: 99%